2016
DOI: 10.1097/sap.0000000000000673
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of BMI on Outcomes Following Complex Abdominal Wall Reconstructions

Abstract: Patients undergoing CAWR with BMIs greater than 30 kg/m have significantly higher rates of skin necrosis, hernia recurrence, and reoperation compared with subgroups of lower BMI. Rates of overall complications among all BMI groups are similar, although trended up with BMI. Surgeons should weight the risks and benefits of CAWR in patients with higher BMIs to reduce specific postoperative complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(19 citation statements)
references
References 13 publications
0
18
0
1
Order By: Relevance
“…Abdominal wall reconstruction surgeries continue to be challenging, and complication and recurrence rates range from 20% to 63% 2,13 . The number of patients with complications found in our series (4, 22.2%) was similar to that found in previous studies (Figures 9 and 10).…”
Section: Discussionmentioning
confidence: 99%
“…Abdominal wall reconstruction surgeries continue to be challenging, and complication and recurrence rates range from 20% to 63% 2,13 . The number of patients with complications found in our series (4, 22.2%) was similar to that found in previous studies (Figures 9 and 10).…”
Section: Discussionmentioning
confidence: 99%
“…A study published in 2016 reviewed 313 patients who underwent complex hernia repair analyzed the effect of obesity over a 15.6 month follow-up. They divided the population based on BMI according the World Health Organization (WHO) classification and found a significantly higher risk of hernia recurrence and reoperation in patients with increasing BMI [61]. Contrary to this, a more recent larger study from the MD Anderson group including 511 patients with a longer mean follow-up of 32 months demonstrated that class 1 or higher obesity does not affect hernia recurrence rates.…”
Section: Preoperative Optimizationmentioning
confidence: 94%
“…The reduction of postoperative incisional hernias and wound complications with laparoscopic gastric bypass motivated development of the technique [17] . However, the risk of hernia recurrence has been shown to positively correlate with increased body mass index (BMI) regardless of the type of repair performed [18][19][20] . While excess weight must be addressed with patients desiring hernia repair, it is not feasible to expect all hernia patients to achieve ideal weight prior to an operation.…”
Section: Obesitymentioning
confidence: 99%